Covid Tracking Apps, Over Reliance on Technology, Bias and Unfairness - Hilcenko, Christine; Taubman-Bassirian, Tara; Kovacic, Zoran (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Various contact tracing apps tracking the spread of the pandemic were issued in different countries. Mainly based on two technologies, centralised with more control by the governments or decentralised controlled by the Apple or Google Android mobile phone systems. In this paper, we will discuss the advantages and disadvantages of the different systems, as well as their potential dangers.
Keywords: privacy; individual freedom; security; information